2021
DOI: 10.1371/journal.pone.0246594
|View full text |Cite
|
Sign up to set email alerts
|

An updated systematic review and meta-analysis on efficacy of Sofosbuvir in treating hepatitis C-infected patients with advanced chronic kidney disease

Abstract: Sofosbuvir seems to be a revolutionary treatment for Hepatitis C-infected patients with advanced chronic kidney disease (CKD) but existing evidence is not quite adequate. The aim of this study was to evaluate the efficacy and safety of Sofosbuvir-based therapy without Ribavirin for all hepatitis C virus genotypes among patients with advanced CKD. We conducted an updated systematic literature search from the beginning of 2013 up to June 2020. Sustained virologic response (SVR) rate at 12 and/or 24 weeks after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Poustchi et al (23) pointed out that even though there was no pharmacokinetic data indicating plasma level of SOF, administration of SOF/DCV in Iranian hemodialysis patients with HCV infection and renal impairment was proved to be safe without observation of any serious adverse event, which is in line with our results. A metaanalysis (24) showed that SOF-based regimens are effective, with a 97% SVR12 rate, in patients with advanced CKD. In this meta-analysis, the efficacy of SOF/DCV in patients with advanced CKD was 97%, which is consistent with the results of the current study (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poustchi et al (23) pointed out that even though there was no pharmacokinetic data indicating plasma level of SOF, administration of SOF/DCV in Iranian hemodialysis patients with HCV infection and renal impairment was proved to be safe without observation of any serious adverse event, which is in line with our results. A metaanalysis (24) showed that SOF-based regimens are effective, with a 97% SVR12 rate, in patients with advanced CKD. In this meta-analysis, the efficacy of SOF/DCV in patients with advanced CKD was 97%, which is consistent with the results of the current study (24).…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis (24) showed that SOF-based regimens are effective, with a 97% SVR12 rate, in patients with advanced CKD. In this meta-analysis, the efficacy of SOF/DCV in patients with advanced CKD was 97%, which is consistent with the results of the current study (24). Dual administration of DCV and SOF daily demonstrated a noticeable effect in the course of 12-week treatment in HCV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Renal clearance is the major elimination pathway for GS-331007, the dephosphorylation-derived nucleoside metabolite of sofosbuvir, and was initially not recommended for patients with severe renal impairment (eGFR <30 mL/minute/1.73m 2 ) or ESRD. However, two meta-analyses of studies on the outcome of the sofosbuvir-based regimen in stage 4–5 CKD 58 , 59 showed a pooled SVR12 rate of 97% with an 11–12% average pooled incidence of adverse effects. Thus, dialysis and advanced renal disease do not require a dose adjustment of DAAs.…”
Section: P Retransplant a Ssessmentmentioning
confidence: 99%
“…These new treatments, direct‐acting antivirals (DAAs), are now administered as an all‐oral, interferon‐free regimen covering all HCV genotypes 1,2 . The DAA regimens have also proven to be efficacious in multiple chronic hepatitis C (CHC) subpopulations including those with cirrhosis, HIV, and with other liver diseases 1–7 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 The DAA regimens have also proven to be efficacious in multiple chronic hepatitis C (CHC) subpopulations including those with cirrhosis, HIV, and with other liver diseases. [1][2][3][4][5][6][7] In addition to providing clinical benefit, DAA-based treatment for CHC has been shown to significantly improve health-related quality of life and other patient-reported outcomes (PROs) which can occur as early as 2-4 weeks after starting treatment even in the presence of advanced liver disease. [8][9][10] The economic benefit of treating all patients with DAAs, especially earlier in their disease course, is also substantial.…”
Section: Introductionmentioning
confidence: 99%